Deformed wing virus prevalence in solitary bees put to the test: an experimental transmission study - Schauer, Alexandria; Bianco, Nadia; Yañez, Orlando; Brown, Andrew; Albrecht, Matthias; Neumann, Peter (Frontiers in Ecology and Evolution, 2023)
Virus spillover from managed to unmanaged bees and vice versa may be one mechanism driving colony losses of the former and declines of the latter. There is clear evidence that the ubiquitous Deformed wing virus (DWV) is a major driver of honey bee (Apis mellifera) colony mortality. Although DWV has been detected in the solitary bee Osmia bicornis, data on DWV infectivity and virulence from solitary bees are scarce. Here, we used microinjection to investigate whether DWV genotype A (DWV-A) obtained from honey bees can replicate in O. bicornis. DWV-A titers and intermediate strand analyses suggest that DWV-A does not replicate in O. bicornis and thus is probably not infectious for this solitary bee species. Interestingly, the data demonstrate that DWV-A recovered from O. bicornis 16 days post-microinjection remains infectious for A. mellifera. Therefore, despite the lack of apparent virulence of DWV in this solitary bee species, O. bicornis has the potential to act as a virus spillover host and may contribute to increased colony losses of managed honey bees and declines in populations of other managed or unmanaged bee species.